A Systematic Hardware Sharing Method for Unified Architecture Design of H.264 Transforms. (10th September 2015) - Chen, Po-Hung; Chen, Hung-Ming; Lin, Ing-Chao
Abstract : Multitransform techniques have been widely used in modern video coding and have better compression efficiency than the single transform technique that is used conventionally. However, every transform needs a corresponding hardware implementation, which results in a high hardware cost for multiple transforms. A novel method that includes a five-step operation sharing synthesis and architecture-unification techniques is proposed to systematically share the hardware and reduce the cost of multitransform coding. In order to demonstrate the effectiveness of the method, a unified architecture is designed using the method for all of the six transforms involved in the H.264 video codec: 2D 4 × 4 forward and inverse integer transforms, 2D 4 × 4 and 2 × 2 Hadamard transforms, and 1D 8 × 8 forward and inverse integer transforms. Firstly, the six H.264 transform architectures are designed at a low cost using the proposed five-step operation sharing synthesis technique. Secondly, the proposed architecture-unification technique further unifies these six transform architectures into a low cost hardware-unified architecture. The unified architecture requires only 28 adders, 16 subtractors, 40 shifters, and a proposed mux-based routing network, and the gate count is only 16308. The unified architecture processes 8 pixels/clock-cycle, up to 275 MHz, which is equal to 707 Full-HD 1080 p frames/second.